RESILIENSI BANK UMUM DI TENGAH KETIDAKPASTIAN EKONOMI GLOBAL - Nurimansyah Setivia Bakti; Mohammad Sofyan; Handaru Agnyana; Umul Wahrul Anwar (JURNAL ILMIAH EDUNOMIKA, 2026)
Global economic uncertainty caused by financial crises, geopolitical shifts, and market fluctuations has a significant impact on the stability of the banking system. This study aims to analyze the resilience of commercial banks in Indonesia in responding to these external pressures by examining factors that influence financial performance and credit risk. The research employs a quantitative descriptive analysis with a population consisting of 105 commercial banks operating in Indonesia. The findings indicate that risk management plays a crucial role in identifying, measuring, and managing risks associated with global economic uncertainty. Banks must maintain a strong commitment to credit quality, including credit portfolio monitoring, risk assessment, and the management of non-performing loans (NPLs). Credit portfolio diversification is essential for reducing exposure to specific credit risks and enhancing income stability. Ensuring adequate liquidity is also vital to cope with potential liquidity pressures arising from uncertain conditions. Moreover, increasing investment in technology and innovation is necessary to improve operational efficiency, enhance customer experience, and develop new products that meet changing market demands. Compliance with evolving regulations related to global economic uncertainty is important to ensure adherence to applicable legal requirements. Transparent communication with stakeholders including customers, investors, and regulators is needed to build trust and strengthen relationships. The significant growth in third-party funds (DPK) indicates that banks can effectively attract public deposits, which can be utilized to support economic activities through lending. Therefore, strong DPK growth serves as a positive indicator of the intermediation function of conventional commercial banks and contributes substantially to overall economic growth.